ANALISIS FAKTOR PEMBENTUK KEPUTUSAN PEMBELIAN PADA PONSEL NOKIA (Studi Kasus Pada Mahasiswa Fakultas Ekonomika dan Bisnis Undip Semarang) - Aryo Widagdo, Abisatyo; Toto Rahardjo, Susilo (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT Developments in technology and communications are getting ahead. Many mobile phone manufacturers compete to capture the consumer market with various features and completeness are given. Nokia is one of several mobile vendors who are currently competing in the face of many competitors. Judging from the sales from year to year, Nokia has decreased. Then do the research on college students because students often keep abreast of current technology, so that they do not want to miss the time to buy a cell phone in accordance with the present technological developments.This study aims to determine what are the factors that shape decisions on the purchase of this Nokia mobile phone. The data used in this study is the primary data obtained from 100 respondents from the Faculty of Economics and Business, University of Diponegoro Semarang. The data obtained were processed by using a reliability test, test validity, and factor analysis test. In the test there is the concept of factor analysis statistics relating to Bartlett's test of sphericy, Communality, eigenvalue, Factor Loading, Factor matrix, and the Kaiser-Meyer-Olkin After testing, the results obtained from the 26 indicators are indicators of the grouping formed by 7 factors. Form factor in Nokia's purchase decision was the features and specifications include, word of mouth, product durability, application programs, mobility, uniqueness of products, and supporting devices.